2018
DOI: 10.29309/tpmj/2018.25.03.389
|View full text |Cite
|
Sign up to set email alerts
|

Oral Clefts

Abstract: Objectives: The present study was carried out in Malaysia to explore satisfactionof non-syndrome cleft lip and plate (CLP) patients and their parents with treatment outcome.Study Design: Descriptive cross sectional study. Setting: This study was carried out in twotertiary care hospitals of Malaysia, namely Universityof Malaya Medical Centre (UMMC) andHospital Kota Bharu/ Hospital Raja Perumpuan Zainab II (HKB/ HRPZII) during August 2007to March 2009. Materials and Methods: Total eighty three CLP patients (age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Our result showed that clefts occur commonly on the left side (70%), and the left complete cleft was the most common among all possible types of clefts (54%). This result is quite similar to the results reported by Shah et al [15] in Malaysia, Al Omari et al [4] in Jordan, and Abdurrazaq et al [25] in Nigeria. Another study conducted in Pakistan by Elahi et al [26] reported that the left side was more commonly involved in cleft lip-related anomalies, and cleft lip alone was observed more frequently than combined CLP or isolated cleft palate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result showed that clefts occur commonly on the left side (70%), and the left complete cleft was the most common among all possible types of clefts (54%). This result is quite similar to the results reported by Shah et al [15] in Malaysia, Al Omari et al [4] in Jordan, and Abdurrazaq et al [25] in Nigeria. Another study conducted in Pakistan by Elahi et al [26] reported that the left side was more commonly involved in cleft lip-related anomalies, and cleft lip alone was observed more frequently than combined CLP or isolated cleft palate.…”
Section: Discussionsupporting
confidence: 92%
“…Our demographic data showed female predominance in patients with a unilateral cleft, which is compatible with what Shah et al [15] reported in their study as they assessed demographic data on the characterization of oral clefts in Malaysia. They reported that females were more involved in oral cleft conditions than males (56.7% and 43.3%, respectively).…”
Section: Discussionsupporting
confidence: 91%